The Media Workflow Puzzle : How It All Fits Together. - Lennon, Chris (Technologist) (Routledge, 2021)
This edited collection brings together a team of top industry experts to provide a comprehensive look at the entire media workflow from start to finish. The Media Workflow Puzzle gives readers an in-depth overview of the workflow process, from production to distribution to archiving. Pulling from the expertise of twenty contributing authors and editors, the book covers topics including content production, postproduction systems, media asset management, content distribution, and archiving and preservation, offering the reader an understanding of all the various elements and processes that go into the media workflow ecosystem. It concludes with an exploration of the possibilities for the future of media workflows and the new opportunities it may bring. Professionals and students alike looking to understand how to manage media content for its entire lifecycle will find this an invaluable resource.